Essential health services delivery and quality improvement actions under drought and food insecurity emergency in north-east Uganda - Charles Njuguna; Habteyes Hailu Tola; Benson Ngugi Maina; Kwikiriza Nicholas Magambo; Nabunya Phoebe; Evelyne Tibananuka; Florence M. Turyashemererwa; Moses Rubangakene; Kisubika Richard; George Opong; Ssekitoleko Richard; Chris Opesen; et al. (BMC, 2023)
Abstract Background Essential health services can be disrupted due to several naturally occurring public health emergencies such as drought, flood, earthquake and outbreak of infectious diseases. However, little evidence exists on the status of essential health services delivery under the effect of drought and food insecurity. North-east Uganda is severely affected by prolonged drought that significantly affected the livelihood of the residents. Therefore, we aimed to determine the current status of essential health services and quality improvement (QI) actions in health facilities in north-east Uganda. Methods We used a descriptive cross-sectional study design to assess the availability of essential health service and quality improvement activities in drought and food insecurity affected districts of north-east Uganda. We included a total of 150 health facilities from 15 districts with proportionated multistage sampling method. We interviewed health facilities' managers and services focal persons using structured questionnaire and observation checklist. We used a descriptive statistic to analyze the data with SPSS version 22. Results A few health facilities (8.7%) had mental health specialist. There was also lack of capacity building training on essential health services. Considerable proportion of health facilities had no non-communicable diseases (38.3%), mental health (47.0%), and basic emergency obstetric care (40.3%) services. Stock out of essential medicines were observed in 20% of health facilities. There was lack of supportive supervision, and poor documentation of QI activities. Conclusion Essential health service and QI were suboptimal in drought and food insecure emergency affected districts. Human resource deployment (especially mental health specialist), provision of capacity building training, improving non-communicable diseases, mental health and basic emergency obstetric care services are required to improve availability of essential health services. Supporting supply chain management to minimize stock out of medicines, and promoting QI activities are also vital to assure quality of health service in drought and food insecurity affected districts in north-Eastern Uganda.